Respostas
respondido por:
30
= 10ab - [3ab - (ab + 2ab - 5ab) - 8ab]
= 10ab - [3ab - (3ab - 5ab) - 8ab]
= 10ab - [3ab - (- 2ab) - 8ab]
= 10ab - [3ab + 2ab - 8ab]
= 10ab - [5ab - 8ab]
= 10ab - [- 3ab]
= 10ab + 3ab
= 13ab
= 10ab - [3ab - (3ab - 5ab) - 8ab]
= 10ab - [3ab - (- 2ab) - 8ab]
= 10ab - [3ab + 2ab - 8ab]
= 10ab - [5ab - 8ab]
= 10ab - [- 3ab]
= 10ab + 3ab
= 13ab
Ivanna20:
Obrigado.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás